The effect of 8 weeks endurance training and Wild Pistachio supplementation on liver micronutrients in rats - Mehdi Said Yousefi, Parvin Farzanegi, Seyed Javad Mirghani (Journal of Applied Pharmaceutical Science, 2013)
Availability of some minerals in the body is pivotal for human’s health. Micronutrients play a supportive role in physiologic performance and physical activities. Authors have shown that exercise may cause the loss of such minerals via a few mechanisms. Therefore, the present paper aimed at determination of the effect of endurance training and wild pistachio supplementation on liver micronutrients in female rats. 28 rats (6-8 years old and 122-180 gr) were randomly divided into four groups, namely Saline-control (SC), Baneh-control (BC), Saline-training (ST), and Baneh-training (BT). Training groups exercised for 8 weeks (5 days a week, 60 min, 25 m/min on treadmill with 0° slope). The rats were orally fed by saline and pistachio extracts for 4 weeks. Tissue biopsy was performed 72 h following the final training session and after 4 h fasting. Statistical analyses were performed by one-way ANOVA at p≤0.05. A significant difference was detected in amounts of zinc, copper, and calcium between BT group and others (p=0.00). The results obtained from the present study showed that combination of training and pistachio supplementation may improve micronutrients rate after 8 weeks endurance training compared with non-supplemented group.
Keywords: Endurance training, Wild Pistachio extract, micronut